Chronic voluntary wheel running exercise ameliorates metabolic dysfunction via PGC-1α expression independently of FNDC5/irisin pathway in high fat diet-induced obese mice - Chaeeun Cho; Minje Ji; Eunhee Cho; Seon Yi; Jae Geun Kim; Sewon Lee (Journal of Physiological Sciences)
Abstract Exercise is an effective intervention to ameliorate metabolic diseases including obesity and insulin resistance, but the mechanisms involved in the metabolic amelioration have not yet been fully elucidated. This study aimed to determine whether AMPK–SIRT1–PGC-1α–FNDC5/Irisin-UCP1 expression is activated and whether metabolic dysfunction is ameliorated by chronic voluntary wheel running (VWR) in high-fat diet (HFD) induced obese mice. C57BL6J mice were randomly assigned into three groups at the age of 7 weeks for 10 weeks: normal chow diet (CON) group, HFD group, and HFD + VWR group. Chronic VWR ameliorates metabolic parameters and leads to increases in the expression of PGC-1α in the gastrocnemius muscle in HFD-induced obese mice. In contrast, the expression of AMPKα, SIRT1, and FNDC5, or circulating irisin levels did not lead to alteration. Improvement of metabolic health was partly mediated via PGC-1α expression by chronic VWR, but not FNDC5/Irisin pathway in HFD-induced obese mice.